Studies of a large dynamic range SiPM readout ASIC MPT2321-B - Qi Baohua; Liu Yong; Shi Huangchao; Wang Danqi; Zhao Zhiyu; Zhu Hongbo (EPJ Web of Conferences)
A new commercially available SiPM-readout 32-channel ASIC with a large dynamic range has been first tested for the development of future high-granularity calorimeters. The response linearity and the singlephoton calibration have been fully characterised. Beamtests were conducted with high-energy particle beams, crystals, and SiPMs for the quantitative study of its dynamic range. The first results show this chip has an excellent signal-to-noise ratio and a large dynamic range.